Parental Perceptions of Pediatric Fever From Two Medical Centers in Lebanon - Reem Eid; Ramy Touma Sawaya; Andrew Farhat; Pascale Salameh; Sarah El Yaman; Maroun Matar (International Journal of Pediatrics)
Conclusion: While the population of the current study showed similar levels of knowledge as those in studies from different parts of the world, around 50% of the participants showed higher levels of knowledge, thus proving that there is still a need for parental awareness and education regarding the causes of fever, its risks and benefits during disease progression, and appropriate ways of management.